2013
DOI: 10.1021/ac302508f
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Electrochemical DNA Charge Transport: Influence of a Mismatch

Abstract: Charge transfer through DNA is of interest as DNA is both the quintessential biomolecule of all living organisms and a self-organizing element in bioelectronic circuits and sensing applications. Here, we report the temperature-dependent properties of DNA charge transport in an electronically relevant arrangement of DNA monolayers on gold under biologically relevant conditions, and we track the effects of incorporating a CA single base pair mismatch. Charge transfer (CT) through double stranded, 17mer monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 64 publications
18
47
0
Order By: Relevance
“…However, for room temperature conformations, each case yields approximately the same average current, which is also comparable to those of the homogeneous sequences. This behavior is consistent with several experimental works, 23,66,67 which showed that that a sequence variation in a homogeneous DNA chain reduces the CT signal at low temperatures, but this effect diminishes as temperature increases. 75 have estimated that the coherent CT is relevant only over distances of about 3 bp, but the low value of the decay parameter taken together with extended delocalized regions indicates that coherent transport is relevant over much longer distances.…”
Section: Chipssupporting
confidence: 93%
“…However, for room temperature conformations, each case yields approximately the same average current, which is also comparable to those of the homogeneous sequences. This behavior is consistent with several experimental works, 23,66,67 which showed that that a sequence variation in a homogeneous DNA chain reduces the CT signal at low temperatures, but this effect diminishes as temperature increases. 75 have estimated that the coherent CT is relevant only over distances of about 3 bp, but the low value of the decay parameter taken together with extended delocalized regions indicates that coherent transport is relevant over much longer distances.…”
Section: Chipssupporting
confidence: 93%
“…This sharp drop correlates with the onset of the melting transition of this monolayer, consistent with prior reports (see Supporting Information Figure 2). 26,28 Detailed comparison of the T17 and T17-A monolayers reveals that the T17-A sequence SWV peak height grows at a slower rate. To ensure the consistency of this trend of CT yield with temperature, we measured the SWV peak heights with temperature from additional T17 and T17-A monolayers prepared on the same chips (three trials).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We observed a dramatic increase in redox current between 45 and 65 °C (Figure 2 A), consistent with the sudden transition expected during melting of the T2–PM duplex. In the absence of target, instead of the sudden current increase expected from a duplex melting transition, we saw a current increase resulting from increased thermal motion of probe molecules at higher temperatures,23 which in turn results in more frequent interaction between redox reporter molecules and the electrode (Figure S4).…”
Section: Apoe Genotypes and Their Associated Microe‐dash Readoutmentioning
confidence: 94%
“…Fluorescence‐based, solution‐phase methods such as dynamic allele‐specific hybridization (DASH) can, in contrast, distinguish homozygous and heterozygous SNPs by means of melting‐curve analysis in solution phase 20. This has spurred interest in integrating melting‐curve analysis with electrochemical detection, but these efforts have been confounded by difficulties in obtaining accurate electrochemical and temperature measurements with sufficient speed and resolution 2123…”
Section: Apoe Genotypes and Their Associated Microe‐dash Readoutmentioning
confidence: 99%